Evaluating the Impact of a Summer Dropout Prevention Program for Incoming Freshmen Attending an Under-Resourced High School. Issue 2 (2nd April 2016) - Vera, Elizabeth; Shriberg, David; Alves, Alison; Montes de Oca, Jessie; Reker, Kassandra; Roche, Meghan; Salgado, Manuel; Stegmaier, Jessica; Viellieu, Lindsay; Karahalios, Vicky; Knoll, Michael; Adams, Kristen; et al.
Abstract : Low high school completion rates are an ongoing challenge for educators. This study provides the results of an evaluation of a ninth-grade summer transition program offered at a large public school with a high freshman dropout rate. The evaluation consisted of preprogram and postprogram surveys and interviews with 64 incoming freshman participating in the summer program. Significant gains were shown in participants' Sense of School Belonging and Academic Self-Efficacy. Qualitatively, the data suggest that students gained clarity about their career goals, became better informed about what it takes to become a successful student, connected a diploma to their own career goals, and felt more comfortable in the school and with its teachers. The implications of these findings for prevention of school dropout are discussed.